Material processing with fast rise and fall time CO2 laser pulses: New CO2 laser system using an integrated acousto‐optic modulator. Issue 5 (16th June 2021) - Kim, Patrick
Abstract: The recent growth in the organic light‐emitting diode (OLED) market has resulted in substantial investments in the display industry, particularly from South Korean companies, but also recently from Chinese players, and this trend is expected to continue for a further three to four years. This expansion of the display industry has resulted in a growth of USP laser markets due to the requirement for higher power and more precise processing quality. This industry is prepared to pay for better laser‐based solutions which has fueled the demand for shorter pulsed CO2 lasers for film cutting applications. One of the key features required in the market is to minimize the heat effect on the material during the cutting process.